2012
DOI: 10.2478/v10290-012-0009-5
|View full text |Cite
|
Sign up to set email alerts
|

Ex situ conservation of endangered Limonium species in the Bulgarian flora

Abstract: A B S T R A C TNative populations of endemic, rare and threatened Limonium species (L. meyeri, L. bulgaricum, L. latifolium, L. vulgare, L. asterotrichum and L. gmelinii) in Bulgaria were monitored and found seriously declined. To preserve these wild genotypes, an approach involving in vitro propagation of explants isolated from immature inflorescence stems was applied at the Institute of Ornamental Plants, Sofia. The rooted plantlets produced were acclimated and grown outdoors under an optimized cultivation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 18 publications
0
6
0
6
Order By: Relevance
“…Ex situ conservation using tissue cultures, as applied in the case of L. sinensis (Dam et al 2010) or being developed in Bulgaria (Kaninski et al 2012), seems like a feasible option to enhance survival of the species. Etymology:-Named in honour of Dagmar Mucina, the life partner and wife of the first author, in recognition of her indispensable support and her shared passion for the flora of Namaqualand.…”
Section: Resultsmentioning
confidence: 99%
“…Ex situ conservation using tissue cultures, as applied in the case of L. sinensis (Dam et al 2010) or being developed in Bulgaria (Kaninski et al 2012), seems like a feasible option to enhance survival of the species. Etymology:-Named in honour of Dagmar Mucina, the life partner and wife of the first author, in recognition of her indispensable support and her shared passion for the flora of Namaqualand.…”
Section: Resultsmentioning
confidence: 99%
“…When starting from seeds, problems of dormancy may also require additional treatments such as scarification with sulfuric acid (H 2 SO 4 ) [ 90 , 123 ], seed coat removal [ 96 ] or longitudinal cut for Distichlis spicata [ 104 ]. The seeds of Limonium species were stratified in sealed and moistened plastic bags at 4 °C during 45 days before decontamination [ 96 ]. Growth regulators such as kinetin (Kin) and gibberellic acid (GA 3 ) promote seed germination for Plantago species [ 92 , 93 ].…”
Section: Micropropagation Of Halophyte Plantsmentioning
confidence: 99%
“…Another study with S. brachiata showed that the addition of 20 g/L MgCl 2 to double-concentrated MS medium with 0.5 mg/L NAA significantly improved the rooting efficiency [ 63 ], whereas S. europaea rooted better on half-strength MS with activated charcoal and a combination of IBA and Kin [ 64 ]. During in vitro rooting of L. monopetalum , the tolerance to NaCl concentrations up to 10 g/L was observed but the root number was reduced as the NaCl concentration increased [ 96 ]. The effect of sucrose content on Eryngium species was analyzed, and E. maritimum had the highest root number with MS/2 with 1.5% sucrose and 0.1 mg/L IAA [ 73 ].…”
Section: Micropropagation Of Halophyte Plantsmentioning
confidence: 99%
“…During the past decades increasing attention has been focussed on ex situ conservation of rare plant species, and in vitro, seed bank and field collections of endangered plants have been created (Dubova et al 2010;Kaninski et al 2012;Miranto et al 2012;Cristea et al 2013). However, in situ conservation remains to be one of the fundamental methods of species protection.…”
Section: Introductionmentioning
confidence: 99%